High hydrostatic pressure and time effects on hygienic and physical characteristics of natural casings and condiments used in the processing of cured meat sausage. (December 2019) - Fraqueza, M.J.; Martins, C.; Gama, L.T.; Fernandes, M.H.; Fernandes, M.J.; Ribeiro, M.H.L.; Hernando, B.R.; Barreto, A.S.; Alfaia, A.J.I.
Abstract: The effect of high hydrostatic pressure (HHP) on the microbial load and physical properties of natural casings, red pepper ( Capsicum annuum L.) and garlic ( Allium sativum ) paste was studied. HHP treatments were performed according to a Response Surface Design. HHP treatment at 540 MPa/270 s was beneficial to assure natural casings quality and safety. Casings treated with combinations as low as 260 MPa/390 s assured good hygienic status with a reduction (P < .001) of Enterobacteriaceae, E . coli and Pseudomonas to values below 10 cfu/g. Coagulase-negative Staphylococcus (CNS) and LAB were reduced by 4 log cfu/g when 540 MPa/270 s was applied. Treated casings turned slightly whiter but their resistance (FT ) to breakage (i.e. casings structural integrity) was not affected. HHP treatment of red pepper paste was not conclusive for decontamination from yeasts and moulds; the bactericidal effect regarding CNS reduction was very low (<0.5 log cfu/g). Red pepper paste treated with lower pressure during longer time (202 MPa/960 s) presented slight color changes. Highlights: HHP treatment at 540 MPa/270 s was beneficial to assure natural casings quality and safety. Casings treated with combinations as low as 260 MPa/390 s assured acceptable hygienic status. The resistance (FT) to breakage of natural casings (i.e. casings structural integrity) was not affected with HHP treatment. HHP treatment of red pepper paste was not conclusive regarding fungal decontamination.